Endovascular treatment of aneurysms and platinum coil caliber: Study protocol of a randomized, controlled trial. Issue 6 (December 2016) - Ghostine, Jimmy; Khoury, Naim; Cloutier, Francis; Kotowski, Marc; Gentric, Jean-Christophe; Batista, André L; Weill, Alain; Roy, Daniel; Darsaut, Tim E; Raymond, Jean
Background: Endovascular coil embolization of cerebral aneurysms is an effective treatment for the prevention of aneurysm rebleeding after subarachnoid hemorrhage. It is also often used in unruptured aneurysms, but it is associated with aneurysm remnants and recurrences in up to 20%–33% of patients. We hypothesized that better aneurysm occlusion rates can be achieved with coils of larger caliber. Methods: The Does Embolization with Larger coils lead to better Treatment of Aneurysms (DELTA) trial is an investigator-initiated, multicenter, prospective, randomized, controlled clinical trial. To test the hypothesis that 15-caliber coiling systems are superior to 10-caliber coils, 564 patients with aneurysms measuring 4–12 mm will be randomized 1:1 to embolization with either 10-caliber coils exclusively (control group) or the highest safely achievable proportion of 15-caliber coils (intervention group). The primary efficacy endpoint of the trial is the occurrence of a major recurrence or a residual aneurysm at one year. A pilot phase of 165 patients will be conducted to verify feasibility of the coiling strategy, compliance to treatment allocation, safety of a 15-caliber platinum coil embolization strategy, recruitment rates, and the capacity to improve packing density. Discussion: The DELTA trial will test the hypothesis that the use of coils of larger caliber can improve angiographic results of endovascular coiling.